Citizenship training: Rescuing citizenship - Almeida, Kathia Susana (Seven Editora, 2024)
The object highlights that the teenager, from an excluded family, studying in a precarious school, finds in the Young Apprentice Program an opportunity for professionalization. The general objective is to understand the cultural, family and school contexts of adolescentes. The specific objectives are to describe the cultural context; talk about the family scenario; explain the school environment. The methodology highlights that the research in its structure is qualitative, considering that the data collection procedures are classified in the participant observation modality. The results highlight that from the wealth of testimonies heard, it is possible to obtain a change in the reality of young people in view of the opportunity to become professional. Self-esteem, posture, behavior, dress and improved communication with colleagues and institutions were added. These teenagers emphasize the importance of the course in this awakening for the world of work. The conclusion highlights that adolescents, though the Young Apprentice Program, obtain benefits such as better technical quality, inclusion in labor market, social integration, citizenship rescue and citizen formation, building an equitable society. DOI:https://doi.org/10.56238/sevened2024.010-064